Masyarakat Sebagai Pilar Penegakan Hukum: Konstitusi Kritis Warga Negara - Alkaida, Randa; Mariana Sesa, Aloysia; Dwi Andini, Tatia; Nurhasanah, Nurhasanah (Indo-MathEdu Intellectuals Journal, 2024)
This article discusses the role of society as one of the important pillars in law enforcement, particularly in the context of the critical constitution of citizens. This type of research is qualitative research, namely literature study. Data collection is carried out through research literature published through google scholar. Various articles relevant to the focus of research are reviewed and analyzed various findings. In addition, analysis and synthesis are carried out through various relevant book sources. The process of data analysis is carried out qualitatively which consists of data reduction, data presentation, and conclusion drawing. The finding of this study is that people who have a good understanding and awareness of the law can play an active role in supervising and criticizing the implementation of the law by the government and law enforcement officials. Civil society participation is essential to prevent abuse of power and ensure compliance with the constitution. Legal education for the community needs to be improved so that citizens understand their rights and obligations and can participate in the law enforcement process. Community involvement in the legal policy-making process is also needed so that the laws made are in accordance with the needs and sense of justice of the community. Partnerships between governments, law enforcement officials, and civil society are essential to effective and equitable law enforcement